IL-33 Ameliorates the Development of MSU-Induced Inflammation Through Expanding MDSCs-Like Cells - Shang, Ke; Wei, Yingying; Su, Qun; Yu, Bing; Tao, Ying; He, Yan; Wang, Youlian; Shi, Guixiu; Duan, Lihua (Frontiers in Endocrinology, 2019)
Interleukin-33 (IL-33), a member of the IL-1 superfamily, has been shown to play a critical role in many diseases through regulating the immune cells responses, including myeloid-derived suppressor cells (MDSCs). Our previous study demonstrated that IL-33 might play a protective role in kidney injury in gout patients through regulating the lipid metabolism. However, the role of IL-33 in the development of MSU-induced inflammation remains elusive. In this study, an increased IL-33 expression were observed in gout patients, which was positively correlated with inflammatory marker CRP. To explore effects and mechanisms of the increased IL-33 expression in the gout patients, the anti-ST2 antibody and exogenous recombinant IL-33 were used in MSU-induced peritonitis animal model that mimics the human gout. Compared with control group, mice with exogenous recombinant IL-33 significantly ameliorated the inflammatory cells infiltration, while blockage of IL-33 signaling by anti-ST2 had no effect on the development of MSU-induced peritonitis. Furthermore, the crucial inflammatory cytokine IL-1β was markedly decreased in IL-33-treated mice. Besides that, a large number of anti-inflammatory MDSCs with CD11b+Gr1intF4/80+ phenotype was observed in the IL-33-treated mice, and adoptive transfer of IL-33-induced MDSCs (CD11b+Gr1intF4/80+) markedly inhibited the IL-1β production in MSU-induced peritonitis. In conclusion, our data provide clear evidences that the increased expression of IL-33 in the gout patients might due to a cause of self-negative regulation, which inhibits the development of MSU-induced inflammation through expanding MDSCs. Thus, IL-33 might serve as a promising therapeutic target for gout.